Why should surgery for early-onset strabismus be postponed?. Issue 2 (February 1988) - Deller, M.
Abstract : The author presents a continued study of 82 cases of pseudoparalysis of the bilateral rectus muscles in early-onset convergent strabismus following early surgery. Up to 10 years after surgery motor results show that 72% of cases remain within +/- 10 prism dioptres after a single surgical procedure. Sensorial findings corroborate the results of other authors' studies in that binocular association is only achieved in those patients where surgery was carried out at a very young age, not older than 1 year. Surgical procedures consisting of bimedial rectus recession with retroequatorial myopexy are described and the development of alphabetical syndromes and dissociated vertical divergence discussed. The evolution of refraction in these cases is also shown.